Trust in Business Partnership, Case Study: Partnership in Engineering and Information Services - Rajala, Anssi (My University, 2016)
The purpose of this thesis is to review the literature in trust, trust building, and trust in business environment. In addition, the existing level of trust in business partnership is researched as a case study for an international company having a partnerships agreement with an engineering and information management service provider. Further, some main action proposals are discussed based on the theory, and responses from performed questionnaire for employees representing all organizational and experience levels in both companies under interest. The research identified the basic characteristics of trust being benevolence, integrity, and ability. In addition, some preconditions for trust were presented to be such as communication, open information sharing, and capability. It was also discussed that trust is always situational and subjective. The process of trust building was identified to start with individuals, expanding to trust in own company, and only after that, trust in other company and partnership. The research was conducted by a questionnaire sent to 18 respondents in total. The questions were formed to be positive and open ended, giving respondents free word to describe their own opinion and give some examples from real life. In addition, respondents indicated their view over the subject under question by an indicative scale with option to indicate somewhat or strongly negative/positive opinion. The research results were indicating the basic level of trust existing within own company, and between the companies under interest. Regarding the trust within own company, communication, employee’s engagement, and existing bureaucratic processes were pointed out to create some issues. Regarding the trust with other company and partnership, the communication and performing towards common goals were giving some criticism.
Keywords: trust; trust building; partnership; communication; business environment; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|